Causes of the interdecadal transition in interannual variability of summertime intraseasonal rainfall over Southern China - Lu, Wei; Zhu, Yimin; Hu, Yijia; Zhong, Zhong; Ha, Yao (Frontiers in Environmental Science, 2022)
This paper studies the interdecadal transition of interannual variability of summertime intraseasonal rainfall (SIR) over South China (SC). It is found that after the mid-1990s (1995/96), the interannual oscillation of SIR over SC has significantly enhanced. The inner connection and possible physical processes associated with the atmospheric intraseasonal oscillation (ISO) involved in the interdecadal transition of the interannual variability of SIR over SC are discussed. The results show that the “Silk Road” teleconnection wave trains distributed zonally across Eurasia from western Europe to northeastern China in the mid-to-high latitudes and the intraseasonal component of the western Pacific subtropical high (WPSH) are two major factors that control the increase of SIR interannual oscillation over SC after 1996. In the period after 1996, the low-frequency perturbation kinetic energy of the wave activity flux associated with the “Silk Road” teleconnection converges more significantly over SC. At the same time, note that the positive SIR anomaly years tend to be in the El Niño decaying phase, the eastward-propagating Kelvin waves triggered by the warm Indian ocean can promote the development of the western Pacific anticyclonic anomaly, which subsequently strengthens the WPSH effectively. The interannual variability of the WPSH east-west movement increases the low-level intraseasonal change of atmospheric circulation over SC. Low-level circulation anomalies in the low latitudes combined with the dispersion of Rossby wave energy in the mid-to-high latitudes eventually lead to an increased interannual variability of SIR over SC.